Vocational Education and Training Graduates: Challenges in Practical Skills to the Job Market - Shrestha, Basanti Roshan Pradhan (International Journal of Social Sciences and Management, 2016)
The purpose of this study is to describe the challenges facing vocational education and training graduates to the job market. Many studies and research has been done to identify the causes of the problem that vocational graduates are facing after they employed in the job market. But still problems are existing in job market as vocational graduates are facing difficulties to transfer their learning. Hence, it challenges the vocational Education and training system. Therefore, this study also focused on the possible interventions to solve the existing problems that vocational graduates and job markets have been facing. The gap and weak linkage between vocational training providers and job market challenges curriculum design and performance in job. So, Competency based training based curriculum design improve the quality of instruction through experienced instructors and training providers are the possible intervention to fill the gap. Int. J. Soc. Sc. Manage. Vol. 3, Issue-3: 141-145